Odpowiedzi

Najlepsza Odpowiedź!
2010-02-21T19:58:37+01:00
1,
3(a-2) = 3a-6 = 3a+(-6)
-4(x+y) = -4x-4y = -4x+(-4y)
-5(-x+1) = 5x-5 = 5x+(-5)
-3a(1/3-a) = -a+3a²
(t-2s-1)*7 = 7t-14s-7 = 7t+(-14a)+(-7)
1/2(2a-4b+1) = a-2b+½ = a+(-2b)+½
m(2m+3) = 2m²+3m
3p(2r+5p-1) = 6pr+15p²-3p = 6pr+15p²+(-3p)
xy(2x-3y+5) = 2x²y+(-3xy²)+5xy
2.
a+(a-b) = a²+(-ab)
2x-(x+4) = 2x-x-4=x+(-4)
7-(-x+6) = 7+x-6=1+x
-(x+4)+(x-5) = -x-4+x-5= 0x+(-9) = -9
1-(t+p)-(t-2) = 1-t-p-t+2=1+(-2t)+(-p)
-(-y+2)+(-2y-4) = y-2-2y-4=-y+(-6)
2 5 2
2010-02-21T20:08:13+01:00
Zad 1.
3(a-2) = 3a-6 = 3a+(-6)
-4(x+y) = -4x-4y = -4x+(-4y)
-5(-x+1) = 5x-5 = 5x+(-5)
-3a(1/3-a) = -a+3a²
(t-2s-1)*7 = 7t-14s-7 = 7t+(-14a)+(-7)
1/2(2a-4b+1) = a-2b+½ = a+(-2b)+½
m(2m+3) = 2m²+3m
3p(2r+5p-1) = 6pr+15p²-3p = 6pr+15p²+(-3p)
xy(2x-3y+5) = 2x²y-3xy²+5xy 2x²y+(-3xy²)+5xy

zad 2.
a+(a-b) = a²+(-ab)
2x-(x+4) = 2x-x-4 = x+(-4)
7-(-x+6) = 7+x-6 = 1+x
-(x+4)+(x-5) = -x-4+x-5 = 0x+(-9) = -9
1-(t+p)-(t-2) = 1-t-p-t+2 = 1+(-2t)+(-p)
-(-y+2)+(-2y-4) = y-2-2y-4 = -y+(-6)
4 3 4